Aspects de la Résistance dans les Poudreries - Yves Ploux; Anne Ploux; Guillaume Pollack (L'Atelier du CRH)
The history of the French Resistance also comprises tracking individual trajectories and experience of underground life, on the tiniest scale, including intimacy. This article first covers the repeated attempts of the Ploux family -the husband, Marc, works in a powder mill in Finistère- to get to England and their failures. Then it studies the individual actions in order to hamper the German efforts and the synergies reached through broader organisations, the networks, by the secret services of the Allies and of the Free French, but always fragile. It also takes the own role of women and children in the Resistance. Finally, it brings about further elements on the involvement of a fraction of the graduates of Polytechnique in the Resistance